Movement guidelines for young children: Engaging stakeholders to design dissemination strategies in the Hong Kong early childhood education context - Capio, Catherine M.; Jones, Rachel A.; Ng, Catalina Sau Man; Sit, Cindy H. P.; Chung, Kevin Kien Hoa (Frontiers in Public Health, 2022)
Background Early childhood is a critical period during which patterns of movement behaviors are formed. The World Health Organization had endorsed guidelines for physical activity, sedentary behavior and sleep over a 24-h time period, which had been adopted by the Center for Health Protection of Hong Kong. This paper reports on stakeholder engagements that were conducted to inform the design of strategies to disseminate the guidelines in early childhood education (ECE) settings. Methods Using a mixed-methods study design, we sought to (a) assess the stakeholders' levels of awareness and knowledge of the Hong Kong movement guidelines for young children and (b) identify the factors that influence the uptake of the said guidelines. We conducted an online survey of early childhood education teachers (N =314), twelve focus groups involving teachers (N = 18) and parents (N = 18), and individual interviews of key informants (N = 7) and domestic workers who provide care for preschool-aged children (N = 7). Descriptive statistics were used for the quantitative data, and thematic analysis was performed on the qualitative data using an inductive and semantic approach following a realist framework. Findings Our findings show that teachers were aware of the movement guidelines for young children, but their knowledge of the specific guidelines was deficient; parents and domestic workers had limited awareness and knowledge of the guidelines. Uptake of the movement guidelines is enabled by parent engagement, activities in the ECE centers, home-school cooperation, and community activities for children. The challenges include the time poverty of parents, local curriculum requirements, limited physical spaces, social values, and pandemic-related restrictions. Conclusion We recommend that dissemination strategies in the ECE context should deliver knowledge content and support stakeholders in mitigating the challenges associated with time, space, and social conditions.